1995
DOI: 10.1111/j.1432-1033.1995.059_c.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Genes Coding for a Similar Four‐Cysteine Motif of the Amino‐Terminal Propeptide of a Sea Urchin Fibrillar Collagen

Abstract: We report the characterization of the 5' region of the gene coding for the 2n fibrillar collagen chain of the sea urchin Parcicenrrot~is lividus. This sequence analysis identified the intron/exon organization of the region of the gene coding for the signal peptide, the cysteine-rich domain and the 12 repeats of the four-cysteine module of the unusually long amino-propeptide. This still unknown four-cysteine motif is generally encoded by one exon, which confirms that the distinct amino-propeptide structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…shown that SURF modules are present in the N-propeptide of the sea urchin 2␣ fibrillar collagen chain and that another part of the sea urchin genome could encode several SURF modules (4,5). Until now, however, we have had no evidence that this region is part of an active gene or pseudogene.…”
Section: The P Lividus Genome Can Potentially Encode Several Proteinmentioning
confidence: 98%
See 1 more Smart Citation
“…shown that SURF modules are present in the N-propeptide of the sea urchin 2␣ fibrillar collagen chain and that another part of the sea urchin genome could encode several SURF modules (4,5). Until now, however, we have had no evidence that this region is part of an active gene or pseudogene.…”
Section: The P Lividus Genome Can Potentially Encode Several Proteinmentioning
confidence: 98%
“…In sea urchin, the N-propeptide consists, from the amino to the carboxyl terminus, of a cysteine-rich region or tsp-2 module, 12 repeats of a four-cysteine domain, and a short triple helical region connected to the N-telopeptide. The four-cysteine module or SURF, 1 for Sea URchin Fibrillar, domain has been described for the first time in the 2␣ fibrillar collagen chain, but the sea urchin genome possesses at least one other region that could potentially encode several SURF modules (4,5). The consensus sequence of this 140 -145 amino acid motif is X (40) GX 2 LWX 11 GXGX 39 CX 6 CX 2 (L/F)X (23) CX (4) CX 1 (where the numbers in parentheses represent an average number of residues).…”
mentioning
confidence: 99%
“…This property has been related to the thin diameter of the fibrils (Linsenmayer et al, 1993;Wu and Eyre, 1995). In the model of Linsenmayer et al (1993), type V molecules are arranged such that their triple-helical domain lies (Lee et al, 1991 ;Exposito et al, 1995). By comparison of the three distinct vertebrate N-propeptide structures and the newly N-propeptide configuration (called structure IV) specific of the sea urchin fibrillar 2a chain, only one subdomain, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The l a chain corresponds to the vertebrate homolog of the proa2(I) chain (Exposito et al, 1992b), and the 3u and 4a chains correspond to two basement membrane type IV collagen chains (Exposito et al, 1993(Exposito et al, , 1994. By in situ hybridization, it has been reported that the four collagen-related genes are expressed in the mesenchymal cell lineage (D'Alessio et al, 1989(D'Alessio et al, , 1990Wessel et al, 1991 ;Exposito et al, 1994). The two type IV related genes begin to be co-expressed at the blastula stage and the two fibrillar collagen genes at the late gastrula stage.…”
mentioning
confidence: 99%
“…Moreover, traces of a homotrimeric 1␣ chain have been described in the sea urchin Paracentrotus lividus (9). The complete primary structure of these two fibrillar collagen chains has been characterized in the sea urchin Strongylocentrotus purpuratus (10,11), whereas partial sequences have been described in P. lividus (12)(13)(14) and Hemicentrotus pulcherrimus (15). The 2␣ chain presents a large N-propeptide region including 12 repeats of an 140 -145 amino acid module that we have named SURF 1 for sea urchin fibrillar module (14).…”
mentioning
confidence: 99%